O incidente de desconsideração da personalidade jurídica como instrumento do capitalismo humanista - Previde, Renato Maso (2019)
To show that the breach of contract or the negligence of law has a connection to the economic crisis discourses, as exemplified by the term “Brazil Cost” (Custo Brasil) and the attempt to go back to old economic systems, that make the rights poorer and that represent the Discourse of Power. The aims of this thesis are in demonstrating that a) the economic problems, by being complex and by reaching the common humanistic interest, claim for a legal answer that is able to protect these common interests, making the Human Rights Letter (Carta dos Direitos Humanos) work, b) the application of only one economic system that can be part of the market interests, knowing that it does not correspond to the answer for this protection of common humanity interest c) The Federal Constitution should be applied in its supremacy so that it could minimize the economic damage in Brazil, mainly when people have this access to the minimum, related to the capital, by itself, the richness is around the economy and, because of that, reversing the economic crisis, d) the application of constitutional economic document so that one of the greatest conquers of our country, the Humanistic Capitalism can be put in use preserving the company, in the terms of ‘company preservation principles’ e) that the infra-constitutional regulation structure itself in the Humanistic Capitalism as an answer to the Discourse of Power made when the struggle against the economic crisis happened or even as an impeachment against the imposition of the simplistic reading of Liberalism. As an application of these aims, this thesis presents, as a justification, the essential application of the article 170 of Federal Constitution, having as a basis the Humanistic Capitalism, theory that was revised by the PhD Professors Ricardo Sayeg and Wagner Balera, used as a theoretical reference for this work. Thinking about all these arguments, the thesis is developed from what follows:1.Is there a mitigation of the Economy, as a Discourse of Power, by the Law?; 2. Does the Humanistic Capitalism target the protection of human common interests in times of economic crisis?; 3. Is there convergence of the recent Code of Civil Procedure with the economic constitutional order and also the Humanistic Capitalism?; 4. Does the incident of negligence of the legal personality make it an instrument of the Humanistic Capitalism? The methodology used in this research was based on the systematic analyses of national and international bibliographies which were the fundament to help to build the ideas presented here. As a result, we came to the conclusion that Law can mitigate the Economy using as a basis the Economy of the country, also based on the economic system capable of generating sustainability between the capital and social distribution of this capital, by the Humanistic Capitalism, and this will automatically generate, by itself, humanized infra-constitutional legislations, in which the citizens will have access to the constitutional principles, as it is the case represented by the negligent procedure of the legal personality, that makes constitutional principles work, from the great defense to the company protection, being essential to the fair response in times of economic crisis